2021
DOI: 10.4314/ijest.v12i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring capability of a Poisson process: Relative goodness of the estimates obtained by different approaches

Abstract: No Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, Yeh and Bhattacharya (1998) proposed ‫ܥ‬ index, Borges and Ho (2001) proposed C u index, Perakis and Xekalaki (2005) presented ‫ܥ‬ index and Maiti et al (2010) suggested ‫ܥ‬ ௬ index for assessment of process capability of attribute process data. Pal and Gauri (2020) assessed relative goodness of these indices and suggested about the best measure of PCI for Poisson process data.…”
Section: Proposed Approach For Computation Of Pci Of a Bivariate Zip ...mentioning
confidence: 99%
“…For example, Yeh and Bhattacharya (1998) proposed ‫ܥ‬ index, Borges and Ho (2001) proposed C u index, Perakis and Xekalaki (2005) presented ‫ܥ‬ index and Maiti et al (2010) suggested ‫ܥ‬ ௬ index for assessment of process capability of attribute process data. Pal and Gauri (2020) assessed relative goodness of these indices and suggested about the best measure of PCI for Poisson process data.…”
Section: Proposed Approach For Computation Of Pci Of a Bivariate Zip ...mentioning
confidence: 99%